In Vitro Susceptibility of Mycobacterium abscessus and Mycobacterium fortuitum Isolates to 30 Antibiotics - Shen, Yaojie (Biomed Res Int, 2018)
OBJECTIVE: Nontuberculous mycobacteria (NTM) cause various diseases in humans and animals. Recently, the prevalence of NTM-related disease has been on the rise, becoming an emerging public health problem. The aim of this study was to determine the antibiotic susceptibility profiles of clinical isolates of Mycobacterium abscessus and Mycobacterium fortuitum. Methods. We performed susceptibility tests on 37 clinical NTM isolates to 30 antibiotics with the microdilution method recommended by the Clinical and Laboratory Standards Institute. RESULTS: Both M. abscessus and M. fortuitum were highly resistant to antitubercular drugs such as isoniazid, rifampin, ethambutol, clofazimine, ethionamide, and rifabutin. M. abscessus showed the lowest resistant rates to cefoxitin (10%), azithromycin (10%), amikacin (10%), and clarithromycin (20%) and very high resistant to sulfamethoxazole, vancomycin, oxacillin, clindamycin, and all fluoroquinolones. M. fortuitum showed low resistance to tigecycline (0%), tetracycline (0%), cefmetazole (12%), imipenem (12%), linezolid (18%), and the aminoglycosides amikacin (0%), tobramycin (0%), neomycin (0%), and gentamycin (24%). CONCLUSION: Amikacin, cefoxitin, and azithromycin have the highest in vitro activity against M. abscessus. Isolates of M. fortuitum need to be individually evaluated for drug susceptibility before choosing an effective antimicrobial regimen for treatment of infections.